MODEL GROUP INVESTIGATION DAN INDUKTIF SEBAGAI ALTERNATIF MENGEMBANGKAN KETERAMPILAN PROSES SAINS DAN BERPIKIR SISWA - Syahmani Syahmani (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2013)
The constructivist paradigm for the instructional design to facilitate not only the thinking processes but also the social interaction processes. As such, Group Investigation and Inductive model in learning science. In Group Investigation (GI) models, learning to work together productively as well as to interact socially and effectively in a small group to problem solving. A variety of skills, for example, interpersonal, problem solving, and study skills would be needed. In Group Investigation and inductive models could sharpen the students‟ ability academically as well as socially; the application of  GI models could increase students‟ activities and process skill during the learning  process science. Futhermore, the students showed their enthusiasm and high motivation in doing their tasks, presentations and discussions. Besides, their attention, concentration, interaction, creativity, cooperation in group and their work in problem solving. Cooperative learning type GI could increase the students‟ achievement in learning Science.In Inductive models, student as center in learning process. Student learning is constructed knowledge and teacher facilitate to true understanding about material learning.  Thus, the GI and inductive models could be applied as one of the alternatives in learning science at school because it could increase the students‟ enthusiasm and also the students‟ learning achievement. Key words: Group investigation and Inductive models, process science skill and thinking